2010
DOI: 10.1083/jcb1891oia2
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral cavernous malformations proteins inhibit Rho kinase to stabilize vascular integrity

Abstract: , reversible by fasudil, a ROCK inhibitor. Furthermore, we show that ROCK hyperactivity occurs in sporadic and familial human CCM endothelium as judged by increased phosphorylation of myosin light chain. These data establish that KRIT1-CCM2 interaction regulates vascular barrier function by suppressing Rho/ROCK signaling and that this pathway is dysregulated in human CCM endothelium, and they suggest that fasudil could ameliorate both CCM disease and vascular leak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
100
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(110 citation statements)
references
References 46 publications
6
100
3
1
Order By: Relevance
“…Previous studies of the CCM pathway have not revealed a molecular path to transcriptional regulation, although changes in RhoA activity (Glading et al, 2007; Stockton et al, 2010; Whitehead et al, 2009; Zheng et al, 2010) and TGFb signaling (Maddaluno et al, 2013) have been reported. The findings that CCM2 interacts with MEKK3 in endothelial cells and that endocardial loss of CCM signaling and MEKK3 confer precisely reciprocal changes in gene expression suggested that the CCM pathway may control gene expression by regulating MEKK3 signaling (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies of the CCM pathway have not revealed a molecular path to transcriptional regulation, although changes in RhoA activity (Glading et al, 2007; Stockton et al, 2010; Whitehead et al, 2009; Zheng et al, 2010) and TGFb signaling (Maddaluno et al, 2013) have been reported. The findings that CCM2 interacts with MEKK3 in endothelial cells and that endocardial loss of CCM signaling and MEKK3 confer precisely reciprocal changes in gene expression suggested that the CCM pathway may control gene expression by regulating MEKK3 signaling (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…How CCM signaling regulates endothelial and vascular function remains unclear. Cell culture studies and pharmacologic studies in mice have linked CCM signaling to negative regulation of RhoA activity (Glading et al, 2007; Stockton et al, 2010; Whitehead et al, 2009; Zheng et al, 2010) and TGFb (Maddaluno et al, 2013), but definitive evidence for a causal relationship to these pathways or other downstream CCM effectors that clearly explain the pathway’s function in vascular development and maintenance has been lacking.…”
Section: Introductionmentioning
confidence: 99%
“…ROCK is a RhoA effector that functions to increase endothelial permeability and cause vascular instability, and ROCK has been further suggested as a drug discovery target for regulation of vascular disorders [18]. Loss of CCM proteins caused RhoA abundance and excessive ROCK activity [6,21,58,63], which were consistently found in not only familial CCM lesions due to loss of function of CCM proteins but also sporadic lesions [58], suggesting much more widespread vascular pathophysiological consequences of sustained and excessive ROCK activity in CCM disease than previously appreciated, and thereby, dysregulation of RhoA/ROCK signaling is highlighted as a significant status of human CCM disease. Accordingly, pharmacological inhibition of ROCK using small-molecule kinase inhibitors, such as fasudil [58] (a drug approved in Japan for cerebral vasospasm treatment with good tolerance [54]), Y-27632 [6], and even simvastatin [63] (a potent drug for lowering cholesterol synthesis also with pleiotropic effect on inhibition of ROCK activity [61]), has been proposed as an additional therapeutic strategy for treatment of symptomatic CCM patients whose therapeutic options are currently limited to brain surgery, which may pose high risk to patients and sometimes suffers from surgical inaccessibility of brain lesions.…”
Section: Potential Role Of Icap-1 In Ccm Pathogenesismentioning
confidence: 99%
“…Besides, these lesions lack the components of organized mature tubular structure of the vasculature such as smooth muscle and tight endothelial cell-cell junctions [20]. The absence of tight endothelial junctions in CCM lesions compromises vascular integrity and thus predisposes to hemorrhage and stroke [25,58].…”
Section: Introductionmentioning
confidence: 99%
“…Loss-of-function mutations in CCM2 result in human cerebral cavernous malformation, a common vascular lesion of the CNS that leads to headaches, seizures, stroke, and intracranial hemorrhage (Labauge et al, 2007). By physically interacting with the first CCM-related gene product KRIT1 (Krev1/Rap1A Interaction Trapped 1, also known as CCM1), CCM2 is coupled to transmembrane receptor heart of glass 1 (HEG1) signaling, which regulates the endothelial cell junction and maintains the vessel integrity (Kleaveland et al, 2009) and is involved in the signal pathway that inhibits small GTPase RhoA and its effector Rho kinase, consequently limiting actin stress fibers and vascular permeability (Borikova et al, 2010;Crose et al, 2009;Stockton et al, 2010;Whitehead et al, 2009). Moreover, CCM2 can organize a large CCM signal complex via association with both Kirt1 and the third CCMrelated gene product PDCD10 (programmed cell death 10, also known as CCM3) (Faurobert and Albiges-Rizo, 2010;Hilder et al, 2007;Voss et al, 2007;Zawistowski et al, 2005), which regulates vascular stability and growth dynamically (Rosen et al, 2013;Zheng et al, 2012).…”
Section: Introductionmentioning
confidence: 99%